2012
DOI: 10.1097/00007890-201211271-00147
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 1b, Randomized, Double-Blind, Parallel Group, Placebo-Controlled, Single-Dose, Pharmacokinetic, Pharmacodynamic, Safety and Tolerability Study of ASKP1240 in de novo Kidney Transplantation

Abstract: Conclusion:While policies focused on uDCD may increase overall DD rates, increases in DD from policies that focus on cDCD come at the expense of DBD. We conclude that cDCD negatively impacts the number of donations from brain dead donors and may lead to an overall reduction in the number of transplants performed due to reduced organ retrieval rates. 2546A Phase 1b, Randomized, Double-Blind, Parallel Group, Placebo-Controlled, Single-Dose, Pharmacokinetic, Pharmacodynamic, Safety and Tolerability Study of ASKP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Additionally, ASKP1240 is another promising anti-CD40 monoclonal antibody that has been shown to be well tolerated without cytokine release syndrome or thromboembolic events in a phase I study in healthy subjects [135]. A separate clinical study in patients following kidney transplantation has demonstrated the safety, tolerability, pharmacokinetics, and pharmacodynamics of ASKP1240 [136].…”
Section: Cd40 and Cd40l Blockade In Kidney Transplantationmentioning
confidence: 99%
“…Additionally, ASKP1240 is another promising anti-CD40 monoclonal antibody that has been shown to be well tolerated without cytokine release syndrome or thromboembolic events in a phase I study in healthy subjects [135]. A separate clinical study in patients following kidney transplantation has demonstrated the safety, tolerability, pharmacokinetics, and pharmacodynamics of ASKP1240 [136].…”
Section: Cd40 and Cd40l Blockade In Kidney Transplantationmentioning
confidence: 99%
“…There was no difference in the incidence of infection based on dose, but B cell CD40 receptor occupancy trended to be prolonged as the dose increased (71). Phase II trials are currently in development (36).…”
Section: Askp1240mentioning
confidence: 99%
“…A clinical trial assessing the bioavailability of ASKP1240 in healthy subjects after intravenous and subcutaneous administration was recently completed in September 2012 and demonstrated that ASKP1240 was well tolerated in the range of 50 to 500 mg, with no evidence of cytokine release syndrome or thromboembolic events. There was no difference in the incidence of infection based on dose, but B cell CD40 receptor occupancy trended to be prolonged as the dose increased ( 71 ). Phase II trials are currently in development ( 36 ).…”
Section: Askp1240mentioning
confidence: 99%